ROTOЯ Transdisciplinary Dialogue and Debate: A Public Engagement Case Study. (20th May 2015) - Powell, Anna; Swindells, Steve
Abstract: In 2011, the University of Huddersfield commenced a partnership with Huddersfield Art Gallery, to offer a public engagement exhibitions programme, entitled "ROTOЯ". Featuring the art and design work of University staff, this series of exhibitions, public events and talks acts as a platform for disseminating and communicating practice-based-research, showcasing a community of artists, designers and curators whose ideas and connective practices migrate and span art and design production. For ROTOЯ, interpretation acts as a pivot between academic research, interpretation and public engagement, where points of intersection are considered and debated from multiple perspectives. In 2013, we hosted a symposium at the Institute of Contemporary Arts, London, which questioned how we measure the role and effects of public engagement in art and design. This paper presents the ROTOЯ public engagement exhibitions programme as a case study of public engagement in light of these questions.